CONFORTO AMBIENTAL EM ESPAÇOS LIVRES URBANOS: UM ESTUDO COMPARATIVO ENTRE DUAS PRAÇAS EM LONDRINA-PR - Leão, Ana Luiza Favarão; Casarim, Mariana Gimenez (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
It is considered that in urban planning, environmental comfort is utterly important for its direct influence in the quality of life of users and on the dynamics of the urban environment (MONTEIRO; ALUCCI, 2010). Therefore, studies related to anthropic influences on urban climates that aim to alleviate the effects of climate change through appropriate urban planning measures, become relevant (MINELLA; RASIA; KRÜGER, 2011). In this scenario, this work has the objective to qualitatively analyze two parks in the central area of the city of Londrina / Paraná, investigating the relationship between environmental comfort, use and permanence in open public spaces. A reflection is made about how the occupation and planning modes of the city influence the environmental comfort and a comparative/qualitative analysis of the environment through a specific tool. It can be concluded that the organization and planning of permeable and shading areas interferes directly in the environmental comfort, consequently in the vitality of these spaces. This research, therefore, presents itself as a contribution to climatic analysis of the open urban space, which in turn will contribute to the study of thermal comfort in urban planning.